INVESTMENT DECISION DETERMINATION: ESG, FINANCIAL CONSTRAINTS, AND PROFITABILITY - Pratiwi, Desy Nur; Pravasanti, Yuwita Ariessa (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The purpose of this research is to examine the role of ESG, financial constraints and profitability on investment decisions. The population used was banking companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2024 period. The sampling method used was purposive sampling, resulting in 19 companies as samples over three periods. This study employed quantitative methods and was categorized as descriptive research with a causal nature. Hypothesis testing employed multiple regression analysis. The results showed that ESG did not increase investor confidence, which ultimately had no effect on investment decisions. Financial constraints and profitability negatively affected investment decisions.